A Targeted Sequencing Assay for Serotyping Escherichia coli Using AgriSeq Technology - Elder, Jacob R.; Fratamico, Pina M.; Liu, Yanhong; Needleman, David S.; Bagi, Lori; Tebbs, Robert; Allred, Adam; Siddavatam, Prasad; Suren, Haktan; Gujjula, Krishna Reddy; DebRoy, Chitrita; Dudley, Edward G.; et al. (Frontiers in Microbiology, 2021)
The gold standard method for serotyping Escherichia coli has relied on antisera-based typing of the O- and H-antigens, which is labor intensive and often unreliable. In the post-genomic era, sequence-based assays are potentially faster to provide results, could combine O-serogrouping and H-typing in a single test, and could simultaneously screen for the presence of other genetic markers of interest such as virulence factors. Whole genome sequencing is one approach; however, this method has limited multiplexing capabilities, and only a small fraction of the sequence is informative for subtyping or identifying virulence potential. A targeted, sequence-based assay and accompanying software for data analysis would be a great improvement over the currently available methods for serotyping. The purpose of this study was to develop a high-throughput, molecular method for serotyping E. coli by sequencing the genes that are required for production of O- and H-antigens, as well as to develop software for data analysis and serotype identification. To expand the utility of the assay, targets for the virulence factors, Shiga toxins (stx1, and stx2) and intimin (eae) were included. To validate the assay, genomic DNA was extracted from O-serogroup and H-type standard strains and from Shiga toxin-producing E. coli, the targeted regions were amplified, and then sequencing libraries were prepared from the amplified products followed by sequencing of the libraries on the Ion S5™ sequencer. The resulting sequence files were analyzed via the SeroType Caller™ software for identification of O-serogroup, H-type, and presence of stx1, stx2, and eae. We successfully identified 169 O-serogroups and 41 H-types. The assay also routinely detected the presence of stx1a, c, d (3 of 3 strains), stx2c-e, g (8 of 8 strains), stx2f (1 strain), and eae (6 of 6 strains). Taken together, the high-throughput, sequence-based method presented here is a reliable alternative to antisera-based serotyping methods for E. coli.